Pulled in Too Many Directions: The Causes and Consequences of Work-Work Conflict. (October 2018) - Wynn, Alison T.; Fassiotto, Magali; Simard, Caroline; Raymond, Jennifer L.; Valantine, Hannah
Previous research has documented the influence of overwork and inflexible hours on work-life conflict for working professionals. In this paper, we build on this literature and explore the novel theoretical concept of work-work conflict, a form of inter-role conflict analogous to work-life conflict. Drawing on 48 in-depth interviews with 42 physicians and survey data of 60 faculty at a prominent west-coast academic medical center, we find that work-work conflict is fueled by institutional structural characteristics. Institutional incentives, the extent of recognition for various work activities, and financial rewards are misaligned, causing physicians to experience competing demands across multiple organizational missions (research, teaching, clinical care, and administration/service). Other industries may face similar conditions leading to work-work conflict. We conclude that work-life interventions are necessary but not sufficient to increase employee satisfaction, and that mechanisms to alleviate work-work conflict must be incorporated in practical solutions to address burnout.